Defining Prolonged Length of Acute Care Stay for Surgically and Conservatively Treated Patients with Spontaneous Intracerebral Hemorrhage: A Population-Based Analysis. (27th March 2016) - Stein, Marco; Misselwitz, Björn; Hamann, Gerhard F.; Kolodziej, Malgorzata A.; Reinges, Marcus H. T.; Uhl, Eberhard
Abstract : Background . The definition of prolonged length of stay (LOS) during acute care remains unclear among surgically and conservatively treated patients with intracerebral hemorrhage (ICH). Methods . Using a population-based quality assessment registry, we calculated change points in LOS for surgically and conservatively treated patients with ICH. The influence of comorbidities, baseline characteristics at admission, and in-hospital complications on prolonged LOS was evaluated in a multivariate model. Results . Overall, 13272 patients with ICH were included in the analysis. Surgical therapy of the hematoma was documented in 1405 (10.6%) patients. Change points for LOS were 22 days (CI: 8, 22; CL 98%) for surgically treated patients and 16 days (CI: 16, 16; CL: 99%) for conservatively treated patients. Ventilation therapy was related to prolonged LOS in surgically (OR: 2.2, 95% CI: 1.5–3.1; P < 0.001 ) and conservatively treated patients (OR: 2.5, 95% CI: 2.2–2.9; P < 0.001 ). Two or more in-hospital complications in surgical patients (OR: 2.7, 95% CI: 2.1–3.5) and ≥1 in conservative patients (OR: 3.0, 95% CI: 2.7–3.3) were predictors of prolonged LOS. Conclusion . The definition of prolonged LOS after ICH could be useful for several aspects of quality management and research. Preventing in-hospital complications could decrease the number of patients with prolonged LOS.